(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2016)
The City of Albany was one of the earliest cities established during the European settlement of what became the United States of America. Albany is a cross roads city located on Hudson River near where the Mohawk River joins the Hudson. It isÂ Â between New York City and Montreal, Canada and it became a Gateway city to the west of the nation when the Erie Canal was opened in 1825. Goods flowed into and through Albany mostly on their way to New York City.